2001
DOI: 10.1126/science.1059188
|View full text |Cite
|
Sign up to set email alerts
|

Spermiogenesis Deficiency in Mice Lacking the Trf2 Gene

Abstract: Modern complex societies exhibit marked resilience to interannual-to- decadal droughts, but cultural responses to multidecadal-to-multicentury droughts can only be addressed by integrating detailed archaeological and paleoclimatic records. Four case studies drawn from New and Old World civilizations document societal responses to prolonged drought, including population dislocations, urban abandonment, and state collapse. Further study of past cultural adaptations to persistent climate change may provide valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
163
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 27 publications
10
163
2
Order By: Relevance
“…68 Unlike TRF2 in Drosophila, zebrafish and Xenopus, mouse TRF2 is not required for embryonic development. 79,80 TRF2 is widely expressed in the adult animal. [61][62][63]65 Mouse TRF2 is essential for spermiogenesis.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Unlike TRF2 in Drosophila, zebrafish and Xenopus, mouse TRF2 is not required for embryonic development. 79,80 TRF2 is widely expressed in the adult animal. [61][62][63]65 Mouse TRF2 is essential for spermiogenesis.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…[61][62][63]65 Mouse TRF2 is essential for spermiogenesis. [79][80][81] It was recently demonstrated that TRF2 works in concert with the tissue-specific TAF7L, which is associated with testis-specific promoters, to regulate a subset of postmeiotic genes directing spermiogenesis. 82 Notably, Drosophila TRF2 has been shown to be involved in differentiation of germ cells of both male and female.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…Although other components of the RNA Polymerase II basal transcription apparatus impact meiosis (Zhang et al 2001;Hiller et al 2004), TAF4b is required for mitosis specifically in gonocytes and spermatogonia. TAF4b appears to be essential for germ cell stem cell differentiation and proliferation, which are required for the maintenance of fertility in adult males.…”
Section: Genes and Development 799mentioning
confidence: 99%
“…Control of spermatogenesis requires specialized transcriptional machinery in multiple species including Drosophila, Xenopus, mouse, and human (Martianov et al 2001;Zhang et al 2001;Wang and Page 2002;Han et al 2003;Hiller et al 2004). These alternative general transcription factors may be direct targets of testis-specific factors or function in the initiation of expression-specific genes in the testis that are expressed from alternative promoters (Sassone-Corsi 2002).…”
Section: Genes and Development 799mentioning
confidence: 99%
See 1 more Smart Citation